Юность пришла: повесть / П. М. Бахтин ; [илл.: А. А. Морозов] - Бахтин Петр Матвеевич (Трудрезервиздат, 1958)
Экземпляры: КХ (20120803) / Инвентарный номер: 228168 / Цена: 2.90 / Сис.шифр: Р2 / Авт.знак: Б 30 / ГРНТИ: 17 / ББК: 84(2)